Sleep characteristics and patterns in elite adolescent athletes - Baharav, A.; Navot-Mintzer, D.; Weisblat, D.; Shargal, E. (The 3rd Wingate Congress of Exercise and Sport Sciences, 2014)
Background: Research results obtained during the last decade indicate that adequate sleep is essential for athletic performance. For instance, Cheri Mah, Stanford University, proved how extended sleep in swimmers as well as in other sports allows improved achievements.